PENGENALAN SEKOLAH ALAM BUKITTINGGI SERTA IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH ALAM BUKITTINGGI - Dinda Hasnah; Jihan Rayuda (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
A natural school is basically a place to study which is based on direct (real) learning in nature. Bukittinggi Natural School applies a learning system to nature, nature is studied to be used as learning (direct practice in nature). In the classroom. For example, sundial, symbiosis, ecosystem. Natural schools are also said to be Islamic schools, . Bukittinggi Natural School is a natural school, there are 4 pillars, namely the leadership pillar, the moral pillar, the entrepreneurship pillar, and the logic pillar.Then the implementation of the independent curriculum at this natural school in Bukittinggi namely the leadership pillar, the moral pillar, the entrepreneurship pillar, and the logic pillar which is then realized in various activities such as market day, camping, backpacking, outbound. Overall, the independent curriculum, which includes PPPP (Project for Strengthening the Profile of Pancasila Students) and PPRA (Project for Strengthening the Profile of Rahmatan Lil Alamin) has been implemented well at the Bukittingi Natural School.